The Zymovars of Vibrio cholerae: Multilocus Enzyme Electrophoresis of Vibrio cholerae - Freitas,Fernanda S (2002)
Zymovars analysis also known as multilocus enzyme electrophoresis is applied here to investigate the genetic variation of Vibrio cholerae strains and characterise strains or group of strains of medical and epidemiological interest. Fourteen loci were analyzed in 171 strains of non-O1 non-O139, 32 classical and 61 El Tor from America, Africa, Europe and Asia. The mean genetic diversity was 0.339. It is shown that the same O antigen (both O1 and non-O1) may be present in several geneticaly diverse (different zymovars) strains. Conversely the same zymovar may contain more than one serogroup. It is confirmed that the South American epidemic strain differs from the 7th pandemic El Tor strain in locus LAP (leucyl leucyl aminopeptidase). Here it is shown that this rare allele is present in 1 V. mimicus and 4 non-O1 V. cholerae. Non toxigenic O1 strains from South India epidemic share zymovar 14A with the epidemic El Tor from the 7th pandemic, while another group have diverse zymovars. The sucrose negative epidemic strains isolated in French Guiana and Brazil have the same zymovar of the current American epidemic V. cholerae.